THE STUDY ON VISITORS' REVISIT INTENTION AT SRAGEN'S BAHULAK MARKET - Juni Trisnowati; Kim Budiwinarto; Giarti Slamet (International Journal of Social Science, 2022)
The purpose of this study was to analyze the effect of market image, word of mouth, and visitor satisfaction on the interest of repeat visits at Pasar Bahulak Sragen. This study took place in the Pasar Bahulak Sragen, with the population being visitors to the pasar Bahulak Sragen where the number cannot be known with certainty. The sample used is 100 respondents, with the sampling technique using accidental sampling. Data was collected by giving questionnaires to the visitors they met. Data analysis techniques used include multiple linear regression analysis, F test, t test and coefficient of determination. The conclusion from the results of data analysis shows that (1) Market image has a significant effect on revisit intention. (2) Word of mouth has a significant effect on revisit intention. (3) Visitor satisfaction has a significant effect on revisit intention. (4) Market image, word of mouth, and visitor satisfaction simultaneously have a significant effect on interest in revisit intention at Pasar Bahulak Sragen.